Hubungan Umur dan Jenis Kelamin Terhadap Keberhasilan PITC (Provider Initiated Testing And Counselling) Pada Pasien TB Di Kota Medan Tahun 2017 - Sity Kunarisasi; Imran Pambudi; Asri Mutiara Putri; Nurhanifah Hamdah (Fakultas Kedokteran UPN Veteran Jakarta Kerja Sama KNPT, 2019)
Tuberculosis is a public health issue. Prevalence of tuberculosis in 2017 is estimated 824.000 cases in which making Indonesia the third country in the world with biggest burden TB and the seventh country with biggest burden in HIV-TB. PITC in primary health care is a Health Ministry program. PITC is the only test and counseling to motivated TB patient to get HIV test. The aim of this study is to analyze relationship between age and gender with the success of PITC in TB patients to know the HIV status at Medan in 2017. Method This research is a descriptive-analytic study with cross-sectional approach. the population in this study is TB patients with age 15-49 years old wo had TB diagnosed either with bacteriologic or clinical in primary health care at Medan in 2017. Medan is chosen because Medan is one of eight cities with the highest burden of TB and HIV in Indonesia, also it has complete recording of TB patients. The sample of this study is all TB patients in primary health care at Medan in 2017 who had PITC in total 2.228 from all TB patients in total 5.039 patients. Data analysis using SPSS to search for p value and Odds Ratio (OR). Result 250 of 2.228 (11,22%) patients is positive in HIV test. Statistics analysis using chi-square test shows p value 0.000 (p<0.05) and OR = 1.905 for relationship between gender and HIV test positive. Also, p value of 0,006 (p<0,05) and OR = 1.459 for relationship between age and HIV test positive. In this study with the implementation of PITC in TB patients in primary health care at Medan there is a relationship between sex and age with HIV infection.